2019
DOI: 10.1039/c9ta03934a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical metal–semiconductor–graphene ternary heteronanostructures for plasmon-enhanced wide-range visible-light photocatalysis

Abstract: A high-performance wide-range visible-light photocatalysis platform was constructed from the intimate coupling of morphology-controlled plasmonic metal nanocrystals, a semiconductor, and graphene in a controlled manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Two symmetrical peaks corresponding to Ti 2p 3/2 (458.6 eV) and Ti 2p 1/2 (464.3 eV) are observed, validating the presence of Ti 4+ in all of the samples. 34 The O 1s XPS patterns (Figure 5b) display two peaks at 529.9 and 531.3 eV, which are ascribed to lattice O (Ti−O) and hydroxyl O (−OH), respectively. 35,36 The binding energies of Ti 2p and O 1s for CVDG-TiO 2 are similar to that of the RGO-TiO 2 composite, suggesting the same electronic interactions between TiO 2 and graphene (CVDG and RGO).…”
Section: Resultsmentioning
confidence: 99%
“…Two symmetrical peaks corresponding to Ti 2p 3/2 (458.6 eV) and Ti 2p 1/2 (464.3 eV) are observed, validating the presence of Ti 4+ in all of the samples. 34 The O 1s XPS patterns (Figure 5b) display two peaks at 529.9 and 531.3 eV, which are ascribed to lattice O (Ti−O) and hydroxyl O (−OH), respectively. 35,36 The binding energies of Ti 2p and O 1s for CVDG-TiO 2 are similar to that of the RGO-TiO 2 composite, suggesting the same electronic interactions between TiO 2 and graphene (CVDG and RGO).…”
Section: Resultsmentioning
confidence: 99%
“…However, excessive RGO sheets beyond 50% caused the decrease in the J st , as a less amount of Na 2 Ti 3 O 7 was involved in the photoanode. Compared with similar photoelectrocatalytic systems (summarized in Table S1), the RGO/Na 2 Ti 3 O 7 have enhanced photoelectrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the plasmon‐induced resonant energy transfer and the radiative relaxation of LSPR are possible mechanisms for the plasmon energy transfer 6,9,10 . The hot electron transfer mechanism, which has been known as the dominant pathway of plasmon energy transfer in plasmonic metal–semiconductor heteronanostructures, 11–13 is ineffective in the case of YSNs due to the absence of intimate contact between the semiconductor and the metal. To facilitate the above processes, the spectral overlap between the LSPR of the plasmonic metal and the band gap absorption of the semiconductor is essential 10 .…”
Section: Figurementioning
confidence: 99%